Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/jfbc.13344
|View full text |Cite
|
Sign up to set email alerts
|

Platycodon grandiflorumroots: A comprehensive study on odor/aroma and chemical properties during roasting

Abstract: Platycodon is a ubiquitous plant widely grown in Asia. This study investigated changes in odor/aroma associated sensory attributes and chemical properties in Platycodon grandiflorum roots upon roasting. Amino acid analysis, electronic tongue analysis, chemical property analysis, volatile compound analysis, GC‐olfactometry‐assisted sensory attributes, and electronic nose analysis were performed. In results, amino acid profiles showed diverse patterns. Electronic tongue analysis somewhat corresponded to the free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 43 publications
2
30
0
Order By: Relevance
“…Although caffeine was found in high concentration in this study, it is known as an odorless compound [ 41 ], and thereby was not perceivable during the sniffing test. A similar trend was also evident in a recent study showing that tridecane existed in the highest concentration, but was not detectable through sniffing test, in Platycodon grandiflorum roots [ 19 ].…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…Although caffeine was found in high concentration in this study, it is known as an odorless compound [ 41 ], and thereby was not perceivable during the sniffing test. A similar trend was also evident in a recent study showing that tridecane existed in the highest concentration, but was not detectable through sniffing test, in Platycodon grandiflorum roots [ 19 ].…”
Section: Resultssupporting
confidence: 83%
“…High-oleic peanut coffee exhibited lower bitterness compared to normal coffee, which may be attributed to a decrease in the phenylalanine ( Table 1 ) and caffeine contents ( Table 2 ) that are associated with bitterness [ 21 ]. Previous studies also demonstrated similar results, showing that changes in phenylalanine and caffeine content upon roasting were linked to the bitterness of Platycodon grandiflorum roots and peanut sprout extracts [ 19 , 30 ]. Peanut coffee showed higher saltiness, umami taste, and sweetness than normal coffee.…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations